Les Relations Université-Entreprise entre l’Etat et le besoin - Leclerc, Michel (Canadian Journal of Higher Education, 1991)
Enhancing the economic value of research lies at the centre of the debate on relations between universities and the private sector. The State, torn between the irresolute attitude of some and the blind enthusiasm of others, has to ponder and provide good reasons to support such relations. In spite of its exultant rhetoric, the actual contribution of private industry to the financing of academic research is much lower than claimed in some circles. Universities, caught in a conflict between their traditional mandate and the new challenges they face, are trying to meet these challenges without losing their raison d'être. Three priorities seem to emerge from the debate: the diffusion and transfer of knowledge, support of basic research and professional training.